CONSTRAINT ANALYSIS OF SWINE FARMING UNDER RASHTRIYA KRISHI VIKAS YOJANA (RKVY) IN ANDHRA PRADESH STATE - A. Lavanya; G. Ganga Raju; J. Suresh; K. Sakunthala Devi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was undertaken to assess the economic impact of Rashtriya Krishi Vikas Yojana (RKVY) project run by AICRP on pigs at Tirupati on the livelihoods of beneficiaries of piggery units. The study was carried out in Chittoor, Nellore, Kadapa and Kurnool districts of Andhra Pradesh state. Data were collected from 30 beneficiaries, who were supplied germplasm under RKVY project. These beneficiaries were purposively selected for impact studies since they have completed 3 years of pig rearing and were personally interviewed for collection of data. The constraints that impede the successful management of swine farms were identified and ranked. The most pressing problem of swine farms was the non-availability of Swill feed which is most important ingredient round the year in required quantities. The other equal important constraint was the accessability to institutional credit agencies. Cost of vaccines was another factor in terms of severity as expressed by the farmers. In addition lack of demand for dreessed pork in rural areas, limited availability of breeding stock were identified. Apart from these major problems there were other constraints too affecting the efficient management of swine farms.